2022
DOI: 10.1080/07853890.2022.2034932
|View full text |Cite
|
Sign up to set email alerts
|

Projection of global burden and risk factors for aortic aneurysm – timely warning for greater emphasis on managing blood pressure

Abstract: Rationale Aortic aneurysm (AA) is a serious condition that largely increases the risk of aortic dissection and sudden death. Exploring the global burden of disease and changes in risk factors for AA is essential for public health policy development. Objective To project the death burden from AA and its attributable risk factors in the following decade based on the epidemiological data over the past 30 years. Methods and Results We analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The study suggests that this trend will continue for the next decade and that high systolic blood pressure will replace smoking as the most important risk factor associated with aortic aneurysm death. A meta-analysis has shown that the risk of rupture in AAA patients with comorbid hypertension was 1.66 times higher than that in patients without comorbid hypertension [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study suggests that this trend will continue for the next decade and that high systolic blood pressure will replace smoking as the most important risk factor associated with aortic aneurysm death. A meta-analysis has shown that the risk of rupture in AAA patients with comorbid hypertension was 1.66 times higher than that in patients without comorbid hypertension [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in our study with quantitative analysis including EAPC and PAF. Based on GDB 2019 study, another research predicted a rebounding tendency in death of aortic, and high SBP would be the major risk factor ( 7 ). However, according to our result, a decreasing trend in ASRD, ASDALYR, and attributable risks was obtained, which means that the burden of aortic aneurysms would have a continuing decline globally.…”
Section: Discussionmentioning
confidence: 99%
“…They focused on the association between healthcare access and quality index (HAQ index) system with aortic aneurysm mortality and YLLs in different incomes and age groups ( 5 ). Associations between estimated average percentage change (EAPC) and burden of aortic aneurysm, human development index (HDI) were found respectively ( 6 ), and aortic aneurysm-related death and attributable risks in the next decade were projected ( 7 ). However, they did extensive efforts on the health epidemiology of aortic aneurysms, and much remains to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic diseases, including aneurysms and dissections, are a leading and growing cause of death worldwide: Globally, the number of aortic aneurysm deaths increased to 172,426 in 2019, a rise of 82.1% compared with 1990 ( 5 ). The climbing death rate is even more pronounced in developing countries, with an increase in median death rate (per 100,000) of 0.71, three times higher than in the developed world, where it is 0.22 ( 6 ).…”
Section: Discussionmentioning
confidence: 99%